Estimation of Population Variance Using Auxiliary Information - Misra, Peeyush Misra (IJRDO -JOURNAL OF MATHEMATICS, 2016)
A generalized estimator representing a class of estimators using auxiliary information in the form of mean and variance is proposed. The expression for bias and mean square error are found and it is shown that the proposed generalized class of estimator is more efficient than few of the estimators available in the literature. An empirical study is also included as an illustration.